Polyacrylonitrile mixed matrix membrane for purification, volume reduction and resource recovery of uranium-containing waste liquid and preparation method thereof

By uniformly distributing MOFs particles and polymers in membrane preparation and performing specific treatments, the problems of uneven distribution and insufficient applicability of MOFs in the membrane are solved, and a hybrid matrix membrane with efficient uranyl ion removal and recycling performance is achieved. , suitable for the treatment of uranium-containing waste liquid.

CN118725376BActive Publication Date: 2024-12-27YANGTZE RIVER DELTA RES INST OF NPU TAICANG +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411225096.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-27
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

In the prior art, MOFs have problems with uniformity and uneven distribution during the film preparation process, resulting in unstable membrane performance and difficult to be suitable for the treatment of uranium-containing waste liquid, resulting in low uranium resource recycling efficiency and large material loss.

Method used

By evenly distributing the MOFs particles in the solvent to form a dispersed solution and mixing with porous polymer and polyacrylonitrile, a uniform film is formed by defoaming and 3D printing or scraping treatment, and finally phase conversion is performed in deionized water and Purification was made to prepare a hybrid matrix membrane with high uranyl selectivity and recycling properties.

Benefits of technology

It has achieved efficient removal of uranyl ions in a wide-domain pH solution, with the uranyl removal rate reaching 15%~99.99%, and remained stable under complex conditions, significantly improving the recovery of uranyl ion and the recycling performance of membrane materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118725376B_ABST
    Figure CN118725376B_ABST
Patent Text Reader

Abstract

Polyacrylonitrile mixed matrix membrane for purification, volume reduction and resource utilization of uranium-containing waste liquid and preparation method thereof. The method involves uniformly distributing MOFs particles in a solvent to obtain a MOFs dispersed solution, adding a porogenic polymer and powdered polyacrylonitrile to the MOFs dispersed solution to obtain a polymer solution, degassing the polymer solution to obtain a degassing polymer solution, 3D printing or scraping the degassing polymer solution to obtain a uniform new membrane, and immersing the new membrane in deionized water for phase inversion and purification after standing, and taking it out to obtain a mixed matrix membrane. The prepared membrane material has good adsorption and removal ability for uranium and has a significant volume reduction effect on the waste liquid in a wide range of uranium-containing waste liquids from 1M nitric acid solution to neutral pH, and exhibits excellent selectivity and good performance in terms of recyclability, showing unique potential in the field of purification, volume reduction and resource utilization of uranium-containing waste liquids in the nuclear industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material preparation, and more specifically to preparing functional membrane materials by using porous metal framework materials (Metal-Organic Frameworks, MOFs) as functional sites, and applying the materials to the purification, volume reduction and resource recovery of complex uranium-containing low- and medium-level radioactive waste liquids over a wide pH range. Background Art

[0002] Nuclear energy is widely regarded as an ideal baseload energy source due to its high energy density, environmental friendliness and operational stability. However, in the nuclear fuel cycle, especially in the research and production of uranium conversion and nuclear fuel elements, low- and medium-level waste liquids containing uranium are often produced. This type of waste liquid is usually highly acidic, radioactive and has a complex chemical composition, which limits its further utilization. Effectively recovering uranium resources in these waste liquids is not only crucial to the safety of the ecosystem, but also the key to ensuring the sustainable development of the nuclear energy industry.

[0003] Membrane separation has the characteristics of easy operation, low energy consumption and high efficiency, and has become one of the most promising technologies for the rational and safe treatment of uranium-containing wastewater. Polyacrylonitrile (PAN) is a good membrane-based material due to its excellent chemical and thermal stability and solvent resistance. However, due to the lack of precise regulation of its pore structure, it is difficult to overcome the disadvantage of poor selectivity in practical applications. Metal Organic Frameworks (MOFs) have the advantages of high crystallinity, modifiability, high porosity and large specific surface area, and can effectively extract uranium from aqueous solutions with complex chemical compositions. These characteristics make MOFs ideal candidate materials for many industrial applications, including membrane separation.

[0004] In the prior art, for example, Patent Document 1 (CN112495200B) discloses a method for preparing a mixed matrix membrane with a high-speed gas transmission channel, and the membrane material prepared by this method also contains MOFs and PAN. However, this technology has the following defects:

[0005] (1) The problem of uniformity of MOFs synthesis and distribution: The MOFs involved in Document 1 are ZIF-8 hollow nanotubes synthesized by using organic ligands 2-methylimidazole and ZnO hollow nanotubes under hydrothermal reaction conditions. This synthesis method is carried out simultaneously with the membrane preparation process, which will lead to the uneven morphology and distribution of the generated MOFs, affecting the performance of the final membrane. In addition, it cannot ensure that all organic ligands and ZnO hollow nanotubes are fully involved in the generation of MOFs, which is likely to lead to the waste of some raw materials and uneven distribution of MOFs, thereby affecting the pore structure and overall performance of the membrane.

[0006] (2) Control difficulties caused by complex process paths: In the preparation method of document 1, a spinning precursor solution containing PAN / PVP / metal salt is first prepared, and nanofibers are formed by electrospinning, and then the nanofibers are calcined to obtain metal oxide hollow nanotubes. After that, these hollow nanotubes are dissolved in DMF solution, and then the organic ligands of MOFs are added for hydrothermal reaction to form ZIF-8 hollow nanotubes. In this process, the generation of MOFs and the mixing of polymer solutions are carried out simultaneously, making the generation and distribution of MOFs susceptible to the reaction conditions and difficult to control, resulting in problems such as uneven material distribution and aggregation, which in turn affects the final performance of the membrane.

[0007] (3) Not suitable for the treatment of uranium-containing waste liquid: Although the membrane material prepared in Reference 1 performs well in gas separation, even if the organic ligand form corresponding to its MOFs is replaced with powdered MOFs, it is difficult to achieve ideal results in the actual treatment of uranium-containing waste liquid. The main problems include difficulty in use, low recovery efficiency and large material loss, which limits its feasibility in recycling.

[0008] Therefore, how to effectively incorporate MOFs into membrane-based materials and develop functional membrane materials with high uranyl selective adsorption efficiency and recyclable properties is crucial to the purification of radioactive waste liquid and the recovery of uranium resources. Summary of the invention

[0009] The purpose of the present invention is to provide a mixed matrix membrane of MOFs and polyacrylonitrile and a preparation method thereof, and in particular to provide a mixed matrix membrane having good selectivity and purification and volume reduction for uranium-containing waste liquid in a wide range of pH value solutions.

[0010] In a first aspect, the present invention provides a method for preparing a mixed matrix membrane for purification, volume reduction and resource utilization of uranium-containing waste liquid, comprising the following steps: (I) uniformly distributing MOFs particles in a solvent to obtain a MOFs dispersed solution, wherein the MOFs include any one of UiO-66-NH2, MOF-808, UiO-66, PHOS-100(Hf) and SZ-3; (II) adding a porogenic polymer and powdered polyacrylonitrile to the MOFs dispersed solution to obtain a polymer solution, wherein the mass of the MOFs accounts for 5% to 95% of the mass of the polyacrylonitrile; (III) degassing the polymer solution to obtain a degassing polymer solution; (IV) 3D printing or scraping the degassing polymer solution to obtain a uniform new membrane; (V) allowing the new membrane to stand and then immersing it in deionized water for phase inversion and purification and taking it out to obtain the mixed matrix membrane.

[0011] According to the first aspect, the solvent comprises N,N-dimethylacetamide and / or N,N-dimethylformamide.

[0012] According to the first aspect, the porogenic polymer includes any one of polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene glycol.

[0013] According to the preferred embodiment of the first aspect, the mass fraction of the polyacrylonitrile in the polymer solution is 10% to 17%, and the mass fraction of the porogenic polymer in the polymer solution is 2.5% to 3.5%.

[0014] According to the first aspect, the polymer solution is obtained by sequentially adding the porogenic polymer and polyacrylonitrile to the MOFs dispersion solution and stirring at a heating temperature of 30 to 80° C. and a rotation speed of 110 rpm for 12 to 24 hours.

[0015] According to the preferred embodiment of the first aspect, the process parameters of the 3D printing include: using a needle with a diameter of 0.2 to 0.5 mm as an extrusion print head, a printing speed of 8 to 20 mm / s, a filling spacing of 0.8 to 1.4 mm, and a printing pressure of 0.2 to 0.5 MPa.

[0016] According to the first aspect, preferably, the advancing speed of the scraper in the scraping process is 8 to 20 mm / s.

[0017] According to the first aspect, the mixed matrix membrane is obtained by placing the nascent membrane at room temperature for 1 to 60 seconds and then immersing it in deionized water for phase inversion and purification for 1 to 3 hours before taking it out.

[0018] In a second aspect, the present invention provides a mixed matrix membrane obtained according to the preparation method described in any one of the first aspects.

[0019] According to the preferred embodiment of the second aspect, the mixed matrix membrane is used for the purification of low- and medium-level uranium-containing waste liquid, and the removal rate of uranyl ions in 1M nitric acid with a pH value of 0 to a 10 ppm uranyl solution with a pH value of 4.5 is 15% to 99.99%.

[0020] According to the preferred embodiment of the second aspect, the mixed matrix membrane has the following characteristics in complex uranium-containing low- and intermediate-level waste liquid: under the interference of coexisting competing ions, the uranyl removal rate is 100%.

[0021] According to the preference of the second aspect, the mixed matrix membrane has the following characteristics in uranium-containing low- and medium-level waste liquid: it operates stably for at least 6 times under the condition of pH=4.5, and the uranyl ion recovery rate is higher than 70%, showing obvious purification, volume reduction and resource utilization effects.

[0022] Compared with the prior art, the mixed matrix membrane prepared by the present invention performs particularly well in the application of nuclear waste treatment. It can not only efficiently remove uranyl ions, but also has excellent selective adsorption performance and recycling performance under a wide range of pH conditions, which is conducive to the application of target products. In short, the present invention provides a new idea and method for the preparation of MOFs mixed matrix membranes and the selection of membrane materials for the treatment of uranium-containing waste liquid in the nuclear fuel cycle, and has broad application prospects.

[0023] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings described in this disclosure are for illustrative purposes only of selected embodiments and not all possible embodiments, and are not intended to limit the scope of the present disclosure.

[0025] Figure 1 A flow chart of the preparation of the mixed matrix membrane of the present invention is shown;

[0026] FIG2 shows the water contact angles of Examples 1 to 4 of the present invention and Comparative Example 1;

[0027] FIG3 shows the water permeation of Examples 1 to 4 of the present invention and Comparative Example 1 under a gas pressure of 0.25 bar;

[0028] FIG4 shows the uranyl removal rate of 5 mL of uranyl ion with a uranyl ion concentration of 10 ppm under the condition of pH=1 in Examples 1 to 4 of the present invention and Comparative Example 1;

[0029] FIG5 shows the FTIR spectra of Examples 4 and 5 of the present invention;

[0030] FIG6 shows the uranyl removal rate of 5 mL of uranyl ion with a uranyl ion concentration of 10 ppm under three different pH conditions in Example 4 and Example 5 of the present invention;

[0031] FIG7 shows the water permeation of Example 4 and Example 5 of the present invention at a pressure of 0.25 bar;

[0032] FIG8 shows the selective adsorption of Example 4 and Example 5 of the present invention at pH=4.5;

[0033] FIG9 shows the recycling performance of Example 4 and Example 5 of the present invention under the condition of pH=4.5;

[0034] FIG10 shows the recovery of uranyl ions in six cycles of use performance of Example 4 and Example 5 of the present invention at pH=4.5;

[0035] FIG11 shows the FTIR spectra of Example 4 and Example 5 of the present invention after six cycles at pH=4.5;

[0036] Fig.12 The SEM images of the fillers of Example 4 and Comparative Examples 1 and 2 of the present invention are shown, wherein (a) shows the UiO-66-NH2 powder morphology of Comparative Example 2, (b) shows the PAN film morphology of Comparative Example 1, and (c) shows the mixed matrix membrane UiO 0.7 @PAN morphology;

[0037] Fig.13 The adsorption-desorption isotherms of Examples 4 and 5 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0038] The embodiments of the present invention will be described in detail below in conjunction with examples. Those skilled in the art will appreciate that the following examples are only preferred embodiments of the present invention, in order to better understand the present invention, and therefore should not be considered to limit the scope of the present invention. For those skilled in the art, the present invention may have various changes and variations, and any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention. The experimental methods in the following examples, unless otherwise specified, are conventional methods; the experimental materials used, unless otherwise specified, are purchased from conventional biochemical reagent manufacturers.

[0039] The present invention generally relates to a mixed matrix membrane obtained by adding metal organic frameworks (MOFs) as porous functional fillers into a polyacrylonitrile (PAN) matrix. Figure 1 The preparation flow chart of the mixed matrix membrane of the present invention is shown. Figure 1 As shown, a general example of the method for preparing the mixed matrix membrane is shown below.

[0040] (I) Formation of MOFs dispersion solution

[0041] The method for preparing the mixed matrix membrane of the present invention has a step of uniformly distributing MOFs particles in a solvent to obtain a MOFs dispersed solution. The purpose of this step is to uniformly disperse the MOFs particles in a selected solvent so that the MOFs particles are well distributed in the solution so as to be uniformly combined with the polymer matrix in the subsequent step.

[0042] Types of MOFs include but are not limited to UiO-66-NH2, MOF-808, UiO-66, PHOS-100 (Hf) and SZ-3, etc. The above MOFs materials can effectively adsorb and separate uranyl ions in wastewater due to their excellent properties such as high crystallinity, high porosity and large specific surface area.

[0043] In the present invention, N, N-dimethylacetamide (DMAC) or N, N-dimethylformamide (DMF) is preferably used as a dispersing solvent, and of course a mixture of the two can also be selected as a dispersing solvent. Such solvents can not only disperse MOFs particles well, but also have good solubility and compatibility with the polymers used in the subsequent steps. Both DMAC and DMF are polar solvents that can effectively disperse MOFs particles and prevent them from agglomerating through interaction with the MOFs surface, thereby ensuring that MOFs particles are uniformly distributed in the polymer matrix in the subsequent membrane preparation process.

[0044] The specific operation steps for forming the MOFs dispersed solution include, for example, slowly adding MOFs particles into a pre-prepared solvent, and then performing ultrasonic treatment to uniformly distribute the MOFs particles in the solution. Ultrasonic treatment can effectively break up the agglomeration of MOFs particles, ensuring that they form a uniform and stable dispersion state in the solution.

[0045] It should be understood that compared to the ZIF-8 hollow nanotubes synthesized under hydrothermal reaction conditions using organic ligand 2-methylimidazole and ZnO hollow nanotubes in document 1 in the background technology, the MOFs particles (such as UiO-66-NH2, MOF-808, UiO-66, PHOS-100 (Hf) and SZ-3) used in the mixed matrix membrane of the present invention are MOFs that have been synthesized and have specific structures and properties before preparing the mixed matrix membrane. By adding it directly to the preparation process of the membrane, it is ensured that it can be evenly distributed in the subsequent polymer solution, providing more stable performance and better membrane function. And the MOFs particles of the present invention are different from ZIF-8 in structure and chemical composition, especially UiO-66-NH2, MOF-808, etc. have different metal nodes and organic ligands, giving them different pore structures, structural stability and surface properties, thereby bringing different physical and chemical properties from ZIF-8. It can not only improve the selectivity and permeability of the membrane, but also has special selectivity and chemical stability in the treatment of nuclear waste liquid, which are particularly critical for the treatment of uranium-containing waste liquid in the nuclear fuel cycle. Secondly, the role of the MOFs particles of the present invention in the treatment of uranium-containing waste liquid does not only rely on pore size screening, but also involves more complex chemical adsorption. Specifically, the adsorption of uranyl ions by the MOFs particles selected by the present invention is achieved by the chemical bonding of the active sites in MOFs with uranyl ions. This chemical adsorption not only relies on the pore size of MOFs to capture uranyl ions, but also relies on the high affinity of the MOFs material itself to uranyl ions. For example, specific functional groups in MOFs (such as carboxyl, amino or phosphate groups) can form strong chemical bonds with uranyl ions, thereby improving the selective adsorption capacity of uranyl ions. In addition, the mixed matrix membrane of the present invention can still show excellent uranyl ion selective adsorption performance (see below) in a wide pH range, which not only relies on the stability of the MOFs structure, but also is related to the high chemical selectivity of MOFs to uranyl ions. In practical applications, uranyl ions in waste liquid may be interfered by other ions or molecules. The MOFs (such as UiO-66-NH2, MOF-808) particles of the present invention can effectively distinguish and preferentially adsorb uranyl ions through their specific chemical properties, thereby achieving purification and resource utilization of waste liquid.

[0046] (II) Formation of polymer solution

[0047] The method for preparing the mixed matrix membrane of the present invention comprises the step of adding a porogenic polymer and powdered PAN to the MOFs dispersed solution formed in step (I) to obtain a polymer solution. This step is to enable the MOFs particles to be evenly distributed in the polymer matrix, so as to provide a good material basis for the subsequent membrane preparation.

[0048] During the formation of the polymer solution, a porogenic polymer is first added to the MOFs dispersed solution. The role of the porogenic polymer is to provide a certain pore structure so that the membrane material finally formed has good water permeability and selectivity. Porosity polymers include, but are not limited to, polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA) and polyethylene glycol (PEG). In the present invention, the mass fraction of the porogenic polymer in the polymer solution is controlled between 2.5% and 3.5% to optimize the pore structure and performance of the membrane. Then PAN powder is slowly added to the MOFs dispersed solution mixed with the porogenic polymer. In the present invention, the mass fraction of PAN in the polymer solution is controlled between 10% and 17% to ensure the mechanical strength and corrosion resistance of the membrane material.

[0049] In the polymer solution, the mass of MOFs accounts for 5% to 95% of the mass of PAN. The selection of this ratio range will affect the performance of the final membrane. A lower MOFs content can ensure the integrity and mechanical strength of the membrane, while a higher MOFs content improves the adsorption efficiency of the membrane to uranyl ions. By adjusting the proportion of MOFs, the present invention can optimize the performance of the membrane material in different application environments.

[0050] Specifically, the polymer solution is obtained by sequentially adding a porogenic polymer and PAN to a MOFs dispersion solution and stirring at a heating temperature of 30 to 80°C and a rotation speed of 110 rpm for 12 to 24 hours. The purpose of heating is to accelerate the dissolution and dispersion of the polymer, while stirring enables the components to be fully mixed in the solution to form a uniform polymer solution. Long-term stirring helps to completely dissolve the polymer and make the MOFs particles evenly distributed throughout the solution to avoid particle aggregation or precipitation.

[0051] It should be understood that the present invention firstly distributes the MOFs particles uniformly in the solvent through step (I) to obtain a stable MOFs dispersed solution, ensuring that the MOFs particles are uniformly distributed in the dispersed solution to avoid agglomeration between the particles. Then, in step (II), a porogenic polymer and powdered PAN are added to the dispersed solution to obtain a polymer solution. Through this method of first dispersing and then mixing, the MOFs particles can maintain a uniform distribution state throughout the solution, thereby improving the selectivity, permeability and other functionality of the membrane.

[0052] (III) Formation of degassing polymer solution

[0053] The method for preparing the mixed matrix membrane of the present invention comprises the step of degassing the polymer solution formed in step (II) to obtain a degassing polymer solution. This step mainly removes bubbles in the polymer solution by standing it to obtain a uniform degassing polymer solution.

[0054] In step (II), the polymer solution is stirred and heated, which easily introduces a large number of bubbles. If these bubbles are not effectively removed, defects will appear in the subsequent membrane forming process, resulting in an uneven structure of the membrane, affecting its mechanical properties and permeability.

[0055] Specifically, the degassing process begins with transferring the polymer solution formed in step (II) from the agitator to a container. The container can be, for example, a container with a large surface area and inert material to reduce the adhesion of bubbles and facilitate the rapid discharge of bubbles. After the transfer is completed, the polymer solution is allowed to stand in the container for a period of time so that the bubbles in the solution gradually rise and are discharged. During the standing process, smaller bubbles will slowly gather into larger bubbles and eventually float to the surface of the liquid and be discharged. The length of the standing time is adjusted according to the viscosity of the solution and the ambient temperature, and is usually left standing for several hours to ensure that all bubbles are fully removed.

[0056] In addition, to further improve the degassing effect, the container can be placed in a reduced pressure environment for treatment. By reducing the ambient air pressure, the bubbles can be promoted to expand and rise, thereby accelerating the degassing process. In some cases, vacuum degassing equipment can also be used to more efficiently remove tiny bubbles in the polymer solution. The entire degassing process needs to be operated with caution to avoid the influence of external vibration or temperature fluctuations on static degassing. The ambient temperature should be kept constant to avoid excessively high temperature that increases the fluidity of the solution and affects the discharge of bubbles; and to avoid excessively low temperature that increases the viscosity of the solution and makes it difficult for bubbles to move.

[0057] (IV) Formation of new membrane

[0058] The method for preparing the mixed matrix membrane of the present invention comprises the step of subjecting the deaerated polymer solution formed in step (III) to 3D printing or doctor blade treatment to obtain a uniform new membrane.

[0059] In some embodiments, the formation of the new film can adopt the DIW (Direct Ink Writing) 3D printing process. This process can accurately control the deposition path and thickness of the polymer solution to form a new film with a complex structure. The 3D printing has the following process parameters: a needle with a diameter of 0.2 to 0.5 mm is used as an extrusion print head, a printing speed of 8 to 20 mm / s, a filling spacing of 0.8 to 1.4 mm, and a printing pressure of 0.2 to 0.5 MPa. The specific implementation process of the DIW 3D printing is shown below.

[0060] (Equipment Preparation)

[0061] Select a needle with a diameter of 0.2 to 0.5 mm and install it on the extrusion print head (i.e., barrel) of the 3D printer. Then load the degassed polymer solution into the barrel of the 3D printer. When filling, it is necessary to ensure that the liquid is well sealed to prevent bubbles from entering the material during the printing process. The presence of bubbles may cause uneven printing and even structural defects, affecting the quality of the final new film. In addition, as a variation, the degassed treatment mentioned in step (III) can be carried out directly in the barrel, which is, for example, the degassed container mentioned in step (III) and can be installed in a 3D printer. By pouring the polymer solution directly into the barrel and then performing a degassed treatment, the generation of bubbles can be further reduced, ensuring that the material has optimal fluidity and uniformity during printing.

[0062] (Printing parameter settings)

[0063] Set the printing speed to 8 to 20 mm / s, and select the appropriate speed to ensure uniform deposition of the material. Set the filling spacing to 0.8 to 1.4 mm, and ensure that the distance between adjacent printing paths can ensure the overall continuity of the new film. Adjust the printing pressure to 0.2 to 0.5 MPa, and select the appropriate air pressure according to the viscosity and fluidity of the polymer solution to ensure stable extrusion of the material.

[0064] (Printing process)

[0065] Start the 3D printer, select the appropriate printing path, and print layer by layer according to the designed new membrane structure. During the printing process, ensure that the distance between the needle and the substrate surface is consistent to maintain a uniform thickness of the membrane. As the printing progresses, control the overlap rate of the printing path to ensure that the membrane layers are tightly combined to avoid structural breaks or discontinuities.

[0066] In some embodiments, the degassing polymer solution can be subjected to a conventional blade coating process to obtain a new film. The specific implementation process of the blade coating process is shown below.

[0067] First, prepare the degassed polymer solution to ensure that the solution is bubble-free and has moderate viscosity. Then pour the polymer solution evenly on one end of the substrate, gently touch the polymer solution with a scraper, and push the scraper evenly at a speed of 8 to 20 mm / s. When pushing the scraper, maintain a certain angle to ensure that the solution is evenly coated on the surface of the substrate to form a uniform film layer. If the film thickness needs to be controlled, the distance between the scraper and the substrate can be adjusted as needed. If the required film thickness is not achieved in one scraping, multiple scrapings can be performed after the first scraping film layer is cured, and the advancement speed and angle are kept consistent for each operation. However, care should be taken to avoid repeated scraping on the undried film layer to prevent damage or unevenness of the film layer.

[0068] In some embodiments, electrospinning technology can also be used to prepare the new membrane. This technology uses electrostatic force to eject the polymer solution from a needle and form nanofibers under the action of an electric field, thereby constructing a membrane structure with high surface area and porosity.

[0069] Specifically, the electrospinning process first requires that the degassed polymer solution be loaded into the syringe of the electrospinning device. The syringe is connected to a high-voltage power supply, which generates a strong electric field by adjusting the voltage. Under the action of the electric field, the polymer solution is gradually stretched and formed into extremely fine fibers. The fibers gradually dry during the spraying process and are randomly deposited on a grounded collection plate, thus forming a fibrous new membrane. The new membrane prepared by electrospinning technology has a unique nanofiber structure, which can provide a higher specific surface area and porosity, making it easier to improve the adsorption performance and permeability of the membrane material. In addition, the formation process of nanofibers allows the membrane material to distribute MOFs particles more evenly, thereby improving the functionality of the membrane.

[0070] In addition, in addition to the DIW 3D printing, blade coating and electrospinning techniques listed above, in possible implementations, membrane making processes such as solution casting, thermally induced phase separation (TIPS) and vapor deposition can also be used to prepare the new membrane of the present application.

[0071] (V) Formation of mixed matrix membranes

[0072] The method for preparing the mixed matrix membrane of the present invention comprises the steps of allowing the newly formed membrane in step (IV) to stand, immersing it in deionized water, performing phase inversion and purification, and taking it out to obtain the mixed matrix membrane.

[0073] In the preparation method of the present invention, the new membrane formed by the DIW 3D printing or scraping method adopted in step (IV) is still in a solid-liquid mixed state with a certain viscosity, and further treatment is required to obtain the final solid phase membrane. Specifically, step (V) includes allowing the formed new membrane to stand for a period of time (e.g., 1 to 60 seconds) so that the membrane surface reaches a certain stable state. Afterwards, the new membrane is immersed in deionized water for phase inversion and purification.

[0074] During the phase inversion process, deionized water as a non-solvent will promote the rapid diffusion of the solvent in the polymer solution, causing the polymer in the new membrane to transform from a solution state to a solid phase membrane. This process can not only shape the membrane structure, but also enhance its mechanical strength and stability. At the same time, deionized water can also effectively remove the residual solvent and small molecule impurities in the membrane, thereby purifying the membrane. The phase inversion and purification process is usually carried out at room temperature and lasts for 1 to 3 hours to ensure the integrity and purity of the membrane structure. During this process, the membrane gradually detaches from the substrate to form an independent mixed matrix membrane with good physical properties and chemical stability, which can meet subsequent application requirements, such as purification, volume reduction and resource recovery of uranium-containing waste liquid. Finally, the mixed matrix membrane after deionized water phase inversion and purification is taken out and stored in a humid environment to obtain a functional membrane material with efficient selective adsorption and good water permeability.

[0075] In order to better understand the present invention, the implementation process of the present invention is further described below based on detailed examples, but it should be understood that the present invention is not limited to these examples.

[0076] (Example 1)

[0077] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0078] (I.I) UiO-66-NH2 was weighed at 10% of the mass of PAN and added to 20 mL of DMAC solvent. UiO-66-NH2 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a UiO-66-NH2 dispersion solution.

[0079] (Ⅱ.Ⅰ) PVP was weighed at 25% of the mass of PAN and added to the UiO-66-NH2 dispersion solution. The mass of PVP was 2.5 times the mass of UiO-66-NH2. Stirring was performed at 110 rpm for 1 h at 40°C to ensure that PVP was completely dissolved. Then PAN was added and stirring was continued under the same conditions (40°C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0080] (III.I) The obtained polymer solution was transferred to a barrel and allowed to stand for 12 h for degassing.

[0081] (IV.I) The feed barrel is equipped with a needle with a diameter of 0.25 mm, which is installed on the DIW 3D printer, so that it moves along the x and y axes at a speed of 15 mm / s on the substrate, the filling spacing is 1 mm, and the printing air pressure is 0.25 MPa. For the embodiment using the traditional scraping method, the scraper is pushed at the same speed of 15 mm / s to form a uniform new film.

[0082] (V.I) The printed new membrane was left to stand at room temperature for 30 s to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 h, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane (abbreviated as UiO 0.1 @PAN).

[0083] (Example 2)

[0084] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0085] (Ⅰ.Ⅱ) UiO-66-NH2 was weighed at 30% of the mass of PAN and added to 20 mL of DMAC solvent. UiO-66-NH2 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a UiO-66-NH2 dispersion solution.

[0086] (Ⅱ.Ⅱ) PVP was weighed at 25% of the mass of PAN and added to the UiO-66-NH2 dispersion solution. The mass of PVP was 83.3% of the mass of UiO-66-NH2. Stirring was performed at 110 rpm for 1 h at 40 °C to ensure that PVP was completely dissolved. Subsequently, PAN was added and stirring was continued under the same conditions (40 °C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0087] (III.II) The obtained polymer solution was transferred to a cylinder and allowed to stand for 12 h for degassing.

[0088] (IV.II) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling spacing of 1 mm and a printing air pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0089] (V.II) The printed new membrane was left to stand at room temperature for 30 s to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 h, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane (abbreviated as UiO 0.3 @PAN).

[0090] (Example 3)

[0091] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0092] (I.III) UiO-66-NH2 was weighed at 50% of the mass of PAN and added to 20 mL of DMAC solvent. UiO-66-NH2 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a UiO-66-NH2 dispersion solution.

[0093] (Ⅱ.Ⅲ) PVP was weighed at 25% of the mass of PAN and added to the UiO-66-NH2 dispersion solution. The mass of PVP was 50% of the mass of UiO-66-NH2. Stirring was performed at 110 rpm for 1 h at 40 °C to ensure that PVP was completely dissolved. Subsequently, PAN was added and stirring was continued under the same conditions (40 °C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0094] (III.III) The obtained polymer solution was transferred to a cylinder and allowed to stand for 12 h for degassing.

[0095] (IV.III) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling spacing of 1 mm and a printing pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0096] (V.III) The printed new membrane was left to stand at room temperature for 30 s to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 h, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane (abbreviated as UiO 0.5 @PAN).

[0097] (Example 4)

[0098] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0099] (I.IV) UiO-66-NH2 was weighed at 70% of the mass of PAN and added to 20 mL of DMAC solvent. UiO-66-NH2 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a UiO-66-NH2 dispersion solution.

[0100] (Ⅱ.Ⅳ) PVP was weighed at 25% of the mass of PAN and added to the UiO-66-NH2 dispersion solution. The mass of PVP was 35.7% of the mass of UiO-66-NH2. Stirring was performed at 110 rpm for 1 h at 40 °C to ensure that PVP was completely dissolved. Subsequently, PAN was added and stirring was continued under the same conditions (40 °C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0101] (III.IV) The obtained polymer solution was transferred to a cylinder and allowed to stand for 12 h for degassing.

[0102] (IV.IV) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling spacing of 1 mm and a printing air pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0103] (V.IV) The printed new membrane was left to stand at room temperature for 30 s to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 h, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane (abbreviated as UiO 0.7 @PAN).

[0104] (Example 5)

[0105] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0106] (I.V) MOF-808 was weighed at 70% of the mass of PAN and added to 20 mL of DMAC solvent. MOF-808 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a MOF-808 dispersed solution.

[0107] (II.V) PVP was weighed at 25% of the mass of PAN and added to the MOF-808 dispersion solution. The mass of PVP was 35.7% of the mass of MOF-808. Stirring was performed at 110 rpm for 1 h at 40 °C to ensure that PVP was completely dissolved. Subsequently, PAN was added and stirring was continued at the same conditions (40 °C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0108] (III.V) The obtained polymer solution was transferred to a cylinder and allowed to stand for 12 h for degassing.

[0109] (Ⅳ.Ⅴ) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling spacing of 1 mm and a printing pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0110] (V.V) The printed new membrane was left to stand at room temperature for 30 seconds to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 hours, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane (abbreviated as MOF). 0.7 @PAN).

[0111] (Example 6)

[0112] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0113] (I.VI) UiO-66-NH2 was weighed at 70% of the mass of PAN and added to 20 mL of DMAC solvent. UiO-66-NH2 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a UiO-66-NH2 dispersion solution.

[0114] (II.VI) PVA was weighed at 25% of the mass of PAN and added to the UiO-66-NH2 dispersion solution. The mass of PVA was 35.7% of the mass of UiO-66-NH2. Stirring was performed at 110 rpm for 1 h at 40 °C to ensure that PVA was completely dissolved. Subsequently, PAN was added and stirring was continued under the same conditions (40 °C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0115] (III.VI) The obtained polymer solution was transferred to a cylinder and allowed to stand for 12 h for degassing.

[0116] (IV.VI) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling spacing of 1 mm and a printing pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0117] (V.VI) The printed new membrane was left to stand at room temperature for 30 seconds to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 hours, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane.

[0118] (Example 7)

[0119] A method for preparing a mixed matrix membrane is provided, and the specific implementation process of the method is shown below.

[0120] (I.VII) UiO-66-NH2 was weighed at 70% of the mass of PAN and added to 20 mL of DMAC solvent. UiO-66-NH2 was uniformly dispersed in DMAC by ultrasonic treatment for 10 to 60 min to obtain a UiO-66-NH2 dispersion solution.

[0121] (II.VII) PEG was weighed at 25% of the mass of PAN and added to the UiO-66-NH2 dispersion solution. The mass of PEG was 35.7% of the mass of UiO-66-NH2. Stirring was performed at 110 rpm for 1 h at 40 °C to ensure that PEG was completely dissolved. Subsequently, PAN was added and stirring was continued at the same conditions (40 °C, 110 rpm) for 24 h to obtain a uniform polymer solution.

[0122] (III.VII) The obtained polymer solution was transferred to a cylinder and allowed to stand for 12 h for degassing.

[0123] (Ⅳ.Ⅶ) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling spacing of 1 mm and a printing pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0124] (V.VII) The printed new membrane was left to stand at room temperature for 30 seconds to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 hours, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a mixed matrix membrane.

[0125] (Comparative Example 1)

[0126] The preparation methods of Comparative Example 1 are similar to those of Examples 1 to 5, except that Comparative Example 1 is a pure polymer film. The specific implementation process of the method is shown below.

[0127] (1) PVP was added to 20 mL of DMAC, stirred at 40°C and 110 rpm for 1 h, then PAN was added and stirred at 40°C and 110 rpm for 24 h. The mass of PVP was 25% of the mass of PAN.

[0128] (2) The obtained polymer solution was transferred to a barrel and allowed to stand for 12 h for degassing.

[0129] (3) A needle with a diameter of 0.25 mm was installed on the feed barrel and mounted on the DIW 3D printer so that it moved along the x and y axes at a speed of 15 mm / s on the substrate, with a filling pitch of 1 mm and a printing air pressure of 0.25 MPa. When using the traditional scraping method, the scraper was advanced at a speed of 15 mm / s.

[0130] (4) The printed new membrane was left to stand at room temperature for 30 seconds to stabilize the membrane structure. Subsequently, the new membrane was immersed in deionized water for phase inversion and purification for 3 hours, and the deionized water was replaced 2-3 times during this period. Finally, the membrane was taken out and stored in a humid environment to obtain a pure polymer membrane (abbreviated as PAN).

[0131] (Comparative Example 2)

[0132] Comparative Example 2 provides a powdered UiO-66-NH2 synthesized by a conventional hydrothermal method. The specific synthesis steps are as follows: First, 5.25 g ZrCl4, 5.628 g 2-aminoterephthalic acid, 42 ml HCl and 630 ml DMF solvent are measured, added to a beaker in sequence, and mixed thoroughly. Then, the mixed solution is evenly divided into a 100 ml polytetrafluoroethylene-lined hydrothermal reactor, the reactor is sealed, and placed in an oven at 120 ° C for 1 day. After the reaction is completed, it is naturally cooled to room temperature, the product is collected by centrifugation, and washed three times with DMF and ethanol in sequence. Finally, the obtained powder sample is vacuum dried at 60 ° C to obtain an orange powdered UiO-66-NH2 product.

[0133] FIG2 shows the water contact angles of Examples 1 to 4 and Comparative Example 1 of the present invention. The hydrophilicity of the membrane was evaluated by testing the water contact angles of UiO@PAN membranes with different UiO-66-NH2 contents. The test results show that the addition of UiO-66-NH2 particles can improve the hydrophilicity of the membrane. The membrane materials obtained in Examples 1 to 4 and Comparative Example 1 are all suitable for water environments.

[0134] FIG3 shows the water permeation of Examples 1 to 4 of the present invention and Comparative Example 1 at an air pressure of 0.25 bar. The test results show a certain correlation with the water contact angle test results in FIG2: the smaller the water contact angle, the better the hydrophilicity of the membrane, and the higher the water permeation. This shows that the addition of MOF particles can not only improve the hydrophilicity of the membrane, but also effectively increase the water permeation of the membrane. Therefore, the preparation method of the present invention can prepare a membrane material with high water permeability.

[0135] FIG4 shows the uranyl removal rate of 5 mL of uranyl ion concentration of 10 ppm under pH=1 conditions for Examples 1 to 4 of the present invention and Comparative Example 1. The experimental results show that the pure polymer membrane has no adsorption effect on the uranyl solution under low acidity conditions. The addition of MOFs particles can make the membrane material have uranyl adsorption capacity, and the uranyl removal rate of Examples 1 to 4 gradually increases, which also shows that the MOFs particles in the mixed matrix membrane are the main factor affecting the membrane material in low acidity solutions. The higher the content of MOFs particles, the better the uranyl adsorption performance of the membrane. Therefore, the preparation of Examples 4 and 5 both selected an addition amount of 70%.

[0136] FIG5 shows the FTIR spectra of Examples 4 and 5 of the present invention. As shown in FIG5, 2245 cm -1 , 1450cm -1 The -C≡N stretching vibration peak in PAN is 1657cm -1 The peak of -C=O stretching vibration in PVP is 656cm -1 The -Zr-O stretching vibration peak in MOF indicates that MOFs, PAN and PVP successfully participated in the preparation process of mixed matrix membranes.

[0137] FIG6 shows the uranyl removal rate of 5 mL of uranyl ion concentration of 10 ppm under three different pH conditions in Example 4 and Example 5 of the present invention. The initial pH value of the solution is one of the important factors affecting the uranyl adsorption performance of the membrane. The present membrane material is mainly used for the purification and recovery of uranium-containing waste liquid under low acidity conditions, so its uranyl adsorption performance in pH=4.5, pH=1 and 1M HNO3 was investigated. The experimental results show that for Example 4 and Example 5, the removal rates of uranyl ions of the two membrane materials in 1M nitric acid (pH=0) to 10 ppm uranyl solutions at pH=4.5 are 15%~99.99%. Specifically, in the pH=4.5 solution, both membrane materials have excellent uranyl adsorption performance, and the uranyl removal rates are close to 100%. As the pH decreases, the uranyl removal rate gradually decreases, indicating that the initial pH value of the solution has a greater influence on the uranyl adsorption performance. Under the same pH conditions, MOF 0.7 The uranyl adsorption performance of @PAN is better than that of UiO 0.7@PAN.

[0138] FIG7 shows the water permeation of Example 4 and Example 5 of the present invention at a pressure of 0.25 bar, indicating that both membranes have high water permeation. 0.7 @PAN has high water permeability and good uranyl adsorption performance.

[0139] FIG8 shows the selective adsorption of Example 4 and Example 5 of the present invention under pH = 4.5. Excess metal ions such as Na + , K + , Cs + , Sr 2+ 、Ni 2+ 、Co 2+ , Mn 2+ , its concentration is 10 times that of U(VI). 0.7 @PAN and MOF 0.7 The uranyl removal rate of @PAN can reach 100% in the system with excess metal ions, while the removal rates of other ions are at a very low level. This indicates that the presence of competing ions has no obvious inhibitory effect on the adsorption of uranium, and also indicates that UiO 0.7 @PAN and MOF 0.7 @PAN maintains high adsorption capacity and selectivity in complex media, such as wastewater with high intensity of competing ions.

[0140] Figure 9 shows the cyclic performance of Example 4 and Example 5 of the present invention under pH = 4.5. The experimental results show that UiO 0.7 @PAN and MOF 0.7 The adsorption capacity of @PAN in uranyl ion single solution did not decrease significantly after 6 cycles. This indicates that UiO 0.7 @PAN and MOF 0.7 @PAN has excellent recycling performance in actual use and can reduce costs.

[0141] Figure 10 shows the recovery rate of uranyl ions in six cycles of use under pH = 4.5 in Example 4 and Example 5 of the present invention. Using 2.5 mL 3M HNO3 as the eluent, the experimental results show that 3M HNO3 solution can be used to + Intense competition for binding sites releases uranyl ions from the membrane surface after adsorption, and the resolution (i.e., uranyl ion recovery) of a single solution is well above 70% over six cycles. Figure 8 and Fig. 9 It shows that UiO 0.7 @PAN and MOF 0.7@PAN is a MOF mixed matrix membrane material that is stable enough to be used at least 6 times and has a volume reduction effect.

[0142] FIG. 11 shows the FTIR spectra of Example 4 and Example 5 of the present invention after six cycles at pH = 4.5. Fig.11 As shown, after six consecutive adsorption-elution cycles, UiO 0.7 @PAN and MOF 0.7 The FTIR spectrum of @PAN is basically consistent with the original sample, further indicating that UiO 0.7 @PAN and MOF 0.7 @PAN has good structural stability and excellent recycling performance.

[0143] Fig.12 The SEM images of the fillers of Example 4 and Comparative Examples 1 and 2 of the present invention are shown, wherein (a) shows the UiO-66-NH2 powder morphology of Comparative Example 2, (b) shows the PAN film morphology of Comparative Example 1, and (c) shows the mixed matrix membrane UiO 0.7 @PAN morphology (prepared by DIW 3D printing). Fig.12 As shown in Figure 2, the UiO-66-NH2 powder in (a) exhibits certain pores, but their distribution is uneven; the surface of the PAN film in (b) is relatively flat and smooth, with no obvious pores. 0.7 @PAN combines the advantages of the first two, showing a higher porosity, the filler is evenly dispersed in the continuous polymer matrix, and a uniform pore structure is formed. 0.7 @PAN not only has higher water permeability ( Figure 3 As shown), it also exhibits better selective adsorption performance ( Figure 8 As shown), it also effectively avoids the uneven distribution of MOF fillers during the membrane preparation process.

[0144] Fig.13 The adsorption-desorption isotherms of Examples 4 and 5 of the present invention and Comparative Example 1 are shown. According to common adsorption isotherms, PAN, UiO 0.7 @PAN and MOF 0.7 The adsorption curve of @PAN corresponds to type IV, indicating the existence of mesoporous structures in the three membranes. In addition, the BET specific surface area of ​​PAN was calculated to be 7.173 m 2 g -1 ,UiO 0.7 @PAN’s BET specific surface area is 32.555 m 2 g -1 , MOF 0.7The BET specific surface area of ​​@PAN is 54.937 m 2 g -1 This result shows that the mixed matrix membrane containing MOF particles has a higher specific surface area and a smaller pore size distribution. Generally speaking, micropores and mesopores in the structure are conducive to increasing the specific surface area of ​​the material. A high specific surface area means that ions can more easily enter the adsorption site and combine with it, thus making the membrane material have better uranyl adsorption performance.

[0145] It can be seen that the mixed matrix membrane prepared by using MOFs particles such as UiO-66-NH2 and MOF-808 as functional fillers in the present invention is significantly different from PAN membrane and powdered UiO-66-NH2 in structure and chemical composition, especially UiO 0.7 @PAN and MOF 0.7 @PAN, through its unique pore structure and high specific surface area, can provide more active sites for the selective adsorption of uranyl ions. In addition, by optimizing the mass ratio of MOFs to PAN, the MOFs particles can be evenly distributed in the membrane, further improving the overall performance of the membrane. This precisely controlled ratio enables the mixed matrix membrane of the present invention to achieve the best balance when adsorbing uranyl ions, thereby surpassing traditional membrane materials in performance.

[0146] More importantly, through the application of DIW 3D printing technology, the mixed matrix membrane of the present invention is precisely controlled in microstructure, forming a uniform and continuous pore distribution, which is difficult to achieve with traditional membrane preparation methods. Through layer-by-layer construction by DIW 3D printing, MOFs are evenly distributed and stably embedded, avoiding the filler agglomeration problem common in other methods. This uniform microstructure not only enhances the selective adsorption capacity of the membrane, but also greatly improves its uranyl ion adsorption performance. Therefore, the mixed matrix membrane prepared based on DIW 3D printing technology has shown significant improvements in both morphology and function, especially in the selective adsorption of uranyl ions in nuclear waste treatment, showing higher efficiency and stability.

[0147] In summary, with carefully selected ingredients, optimized mass ratios, and a unique DIW 3D printing preparation process, the mixed matrix membrane of the present invention exhibits remarkable effects that cannot be foreseen by traditional methods. In particular, in terms of uranyl ion adsorption, traditional membrane materials are limited by pore structure and uneven material distribution, making it difficult to maintain efficient adsorption performance in highly acidic and complex chemical environments. However, the present invention, through comprehensive optimization of materials and processes, not only achieves significant advantages in structure, but also demonstrates outstanding unpredictability in performance, especially in the treatment of complex wastewater, showing excellent selective adsorption of uranyl ions.

[0148] In summary, through Examples 1 to 4, it is shown that the target product can be obtained when the MOFs are 5% to 95% of the mass of PAN. Based on the uranyl adsorption performance, the ratio of PAN to MOFs in Example 4 is preferred. This is because under low acidity conditions, the uranyl adsorption performance of the membrane material mainly depends on the MOFs filler added to the membrane, so that the MOFs mixed matrix membrane has uranyl adsorption performance in a wide pH range, has excellent selective adsorption performance and recycling performance, and is conducive to the application of the target product. By comparing Example 4 with Example 5, it is shown that the preparation method of the mixed matrix membrane is applicable to a variety of different MOFs and has a certain universality.

[0149] The applicant declares that the present invention illustrates the detailed features and detailed methods of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed features and detailed methods, that is, it does not mean that the present invention must rely on the above-mentioned detailed features and detailed methods to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., and other changes made within the knowledge scope of ordinary technicians in the field without departing from the purpose of the present invention, all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a mixed matrix membrane for purification, volume reduction and resource recovery of uranium-containing waste liquid, characterized in that: The following steps are involved: (I) uniformly distributing MOFs particles in a solvent to obtain a MOFs dispersed solution, wherein the MOFs include any one of UiO-66-NH2, MOF-808, UiO-66, PHOS-100(Hf) and SZ-3; (II) adding a porogenic polymer and powdered polyacrylonitrile to the MOFs dispersed solution to obtain a polymer solution, wherein the mass of the MOFs accounts for 5% to 95% of the mass of the polyacrylonitrile, the mass fraction of the polyacrylonitrile in the polymer solution is 10% to 17%, and the mass fraction of the porogenic polymer in the polymer solution is 2.5% to 3.5%; (III) degassing the polymer solution to obtain a degassing polymer solution; (IV) performing DIW 3D printing on the degassed polymer solution to obtain a uniform new membrane, wherein the process parameters of the 3D printing include: using a needle with a diameter of 0.2 to 0.5 mm as an extrusion print head, a printing speed of 8 to 20 mm / s, a filling spacing of 0.8 to 1.4 mm, and a printing pressure of 0.2 to 0.5 MPa; (V) After the nascent membrane is allowed to stand, it is immersed in deionized water for phase inversion and purification and then taken out to obtain the mixed matrix membrane.

2. The preparation method according to claim 1, characterized in that: The solvent includes N,N-dimethylacetamide and / or N,N-dimethylformamide.

3. The preparation method according to claim 1, characterized in that: The porogenic polymer includes any one of polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene glycol.

4. The preparation method according to claim 1, characterized in that: The polymer solution is obtained by sequentially adding the porogenic polymer and polyacrylonitrile to the MOFs dispersion solution and stirring the mixture at a heating temperature of 30 to 80° C. and a rotation speed of 110 rpm for 12 to 24 hours.

5. The preparation method according to claim 1, characterized in that: The mixed matrix membrane is obtained by placing the nascent membrane at room temperature for 1 to 60 seconds and then immersing it in deionized water for phase inversion and purification for 1 to 3 hours before taking it out.

6. A mixed matrix membrane obtained according to the preparation method according to any one of claims 1 to 5.

7. The mixed matrix membrane according to claim 6, characterized in that The mixed matrix membrane is used for purifying low- to medium-level uranium-containing waste liquid, and the removal rate of uranyl ions in 1M nitric acid with a pH value of 0 to a 10 ppm uranyl solution with a pH value of 4.5 is 15% to 99.99%.

8. The mixed matrix membrane according to claim 6, characterized in that The mixed matrix membrane has the following characteristics in complex uranium-containing low- and medium-level waste liquid: under the interference of coexisting competitive ions, the uranyl removal rate is 100%.

9. The mixed matrix membrane according to claim 6, characterized in that The mixed matrix membrane has the following characteristics in uranium-containing medium and low-level waste liquid: it can stably operate for at least 6 times under the condition of pH=4.5, and the uranyl ion recovery rate is higher than 70%.

Citation Information

Patent Citations

  • A method for preparing a hybrid matrix membrane with a high-speed gas transport channel

    CN112495200B

  • Pervaporation desalination asymmetric membrane and preparation method thereof

    CN110479102A

  • Preparation method and application of nano-material and MOF co-modified organic film

    CN111744367A